2005
DOI: 10.1161/01.res.0000174429.00987.17
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Left and Right Ventricular Chamber Geometry Affect Cardiac Vulnerability to Electric Shocks

Abstract: Abstract-Although effects of shock strength and waveform on cardiac vulnerability to electric shocks have been extensively documented, the contribution of ventricular anatomy to shock-induced polarization and postshock propagation and thus, to shock outcome, has never been quantified; this is caused by lack of experimental methodology capable of mapping 3-D electrical activity. The goal of this study was to use optical imaging experiments and 3-D bidomain simulations to investigate the role of structural diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 41 publications
11
165
1
Order By: Relevance
“…In order to be able to simulate post-shock arrhythmogenesis in the ventricles, computational research has managed to overcome tremendous difficulties associated with obtaining solutions of very large systems of unknowns, involving stiff equations and computational meshes of irregular geometry. The results are fascinating [10]. First, active bidomain simulations of activity in the 3D ventricles demonstrated that understanding of shock-induced phenomena acquired in earlier, simpler bidomain studies, such as the causes of the specific pattern of VEP and how the post-shock activations originate, remain valid in the 3D ventricles.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 93%
“…In order to be able to simulate post-shock arrhythmogenesis in the ventricles, computational research has managed to overcome tremendous difficulties associated with obtaining solutions of very large systems of unknowns, involving stiff equations and computational meshes of irregular geometry. The results are fascinating [10]. First, active bidomain simulations of activity in the 3D ventricles demonstrated that understanding of shock-induced phenomena acquired in earlier, simpler bidomain studies, such as the causes of the specific pattern of VEP and how the post-shock activations originate, remain valid in the 3D ventricles.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 93%
“…First, the applied shock drives currents that traverse the myocardium and cause complex polarization changes in transmembrane potential distribution (Sobie et al, 1997). Secondly, post-shock active membrane reactions are invoked that eventually result either in termination of fibrillation in the case of shock success, or in reinitiation of fibrillatory activity in the case of shock Using computer models to analyze the etiology of VEP patterns during the shock application phase revealed that shape, location, polarity, and intensity of shock-induced VEP are determined by both the cardiac tissue structure as well as the configuration of the applied field (Knisley et al, 1999;Rodriguez et al, 2005;Sobie et al, 1997). Based on theoretical considerations VEPs can be classified either as "surface VEP", which penetrates the ventricular wall over a few cell layers, or as "bulk VEP" where polarizations arise throughout the ventricular wall (Entcheva et al, 1999;Trayanova et al, 1998).…”
Section: Current Understanding Of Defibrillation Mechanismsmentioning
confidence: 99%
“…To test this hypothesis, we analyzed the global three-dimensional activity in ventricles with the use of a recently-developed realistic computer model of stimulation/defibrillation in the rabbit heart (Trayanova et al, 2002). Simulations with this model, termed the rabbit bidomain model of defibrillation, have proven invaluable in understanding various aspects of the response of the heart to shocks (Rodriguez et al, 2005). The bidomain model is a continuum representation of the myocardium, which takes into account both intracellular and extracellular current distributions through the myocardium.…”
Section: Introductionmentioning
confidence: 99%